2020
DOI: 10.14283/jpad.2020.65
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtyping of Mild Cognitive Impairment Based on Genetic Polymorphism and Gene Expression

Abstract: Background: Alzheimer’s Disease (AD) is a neurodegenerative brain disease in the elderly. Recent studies have revealed the heterogeneous nature of AD. Mild Cognitive Impairment (MCI) is the prodromal stage of AD. Objectives: In this study, we identified subtypes of MCI based on genetic polymorphism and gene expression. Methods: We utilized the two types of omics data, namely genetic polymorphism and gene expression profiling, derived from 125 MCI patients’ peripheral blood samples from the ADNI-1 dataset. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In our previous study, we applied the SNF method to identify the subtypes of MCI patients in the ADNI-1 dataset, based on integrating genetic polymorphism and gene expression data [ 10 ]. Two MCI subtypes were identified based on our method and were compared by the following factors: the time difference of the conversion from MCI to AD, cognitive scales and sMRI images and significantly enriched pathways based on differentially expressed genes separately.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, we applied the SNF method to identify the subtypes of MCI patients in the ADNI-1 dataset, based on integrating genetic polymorphism and gene expression data [ 10 ]. Two MCI subtypes were identified based on our method and were compared by the following factors: the time difference of the conversion from MCI to AD, cognitive scales and sMRI images and significantly enriched pathways based on differentially expressed genes separately.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the MCI-CPS model was applied to predict MCI-to-AD conversion in three years using multi-modality data, including structural MRI, genotype data and gene expression profiling, based on patients’ MCI subtype. In a previous study [ 10 ], we performed SNF, an integrative clustering of multiple genomic data algorithms, to cluster MCI patients. We conducted experimental studies on subtypes of MCI patients and showed that omics data can define subtypes characterized by biological and clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations